Decision support system for determining pharmacy service quality - Irawan D.; Huda M.; Teh K.S.M.; Ihwani S.S.; Rashid M.H.; Febriana; Maseleno A. (American Scientific Publishers, 2023)
Service quality of a trading company affects the level of customer satisfaction. The better the service quality, the higher the level of customer satisfaction. A high level of satisfaction allows the increase of consumers in the company concerned. Evaluation of service quality at Among Rogo Pharmacy is very necessary because the results of the evaluation can be used as a reference to determine policies related to the efforts in improving service quality. This research was conducted using SAW (Simple Additive Weighting) method. This method was chosen because it was able to select alternatives from a number of alternatives. The intended alternative is the level of service quality, namely: (1) Very Bad, (2) Bad, (3) Fair, (4) Good, (5) Very Good. Evaluation results based on observations of Among Rogo Pharmacy were also calculated along with these alternatives and alternatives whose value close to the calculation service evaluation results at Among Rogo Pharmacy. There were considered true to determine the quality of service at Among Rogo Pharmacy. This system can still be developed again by adding weight of the criteria, or by using other methods. Copyright 2019 American Scientific Publishers All rights reserved.